Author Correction: Value of susceptibility‑weighted imaging for the assessment of angle measurements reflecting hip morphology (Scientific Reports, (2020), 10, 1, (20899), 10.1038/s41598-020-77671-1) - Boeker, Sarah M.; Adams, Lisa C.; Fahlenkamp, Ute Lina; Diederichs, Gerd; Hamm, Bernd; Makowski, Marcus R. (Scientific Reports, 2021)
The original version of this Article omitted affiliations for Marcus R. Makowski. The correct affiliations are listed below Department of Radiology, Charité, Charitéplatz 1, Berlin, Germany Department of Radiology, Technical University of Munich, Ismaninger Str. 22, 81675, Munich, Germany King’s College London, School of Biomedical Engineering and Imaging Sciences, United Kingdom, St Thomas’ Hospital Westminster Bridge Road, London, SE1 7EH, UK The original Article has been corrected.
CRIS-Team Scopus Importer:2023-03-08